2015
DOI: 10.1002/ejoc.201500019
|View full text |Cite
|
Sign up to set email alerts
|

A Diastereoselective Route to trans‐2‐Aryl‐2,3‐dihydrobenzofurans through Sequential Cross‐Metathesis/Isomerization/Allylboration Reactions: Synthesis of Bioactive Neolignans

Abstract: The structure of a nickel complex of imidazoline–aminophenol (IAP) prepared from IAP with Ni(OAc)2 was elucidated as cis‐bis(imidazolineaminophenoxide) [Ni(IAP)2]. The [Ni(IAP)2] complex smoothly promoted catalytic asymmetric 1,4‐addition of 3′‐indolyl‐3‐oxindole to nitroethylene to provide chiral mixed 3,3′‐bisindoles with high enantioselectivities. Mechanistic studies using ESI‐MS analyses suggest that one IAP ligand dissociated from [Ni(IAP)2] to generate the Ni–enolate of 3′‐indolyl‐3‐oxindole. From the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Mitsunobu cyclization followed by oxidative cleavage of the alkene and subsequent reduction with simultaneous global deprotection furnished dihydrodehydrodiconiferyalcohol in 60% overall yield, >95:5 dr and 93:7 er, accomplishing a much more e cient and stereoselective synthesis than previously reported (9 steps, 23% overall yield, >95:5 dr, 93:7 er vs. 12 steps, 1.2% overall yield, >95:5 dr, 62:38 er). 69 To gain some preliminary insight into the reaction mechanism, a series of experiments were conducted (Figure 7). Kinetic experiments revealed that in the transformations of allylbenzenes and 1,4-dienes, allylic C-H bond cleavage might not be the rate-determining step.…”
Section: Resultsmentioning
confidence: 99%
“…Mitsunobu cyclization followed by oxidative cleavage of the alkene and subsequent reduction with simultaneous global deprotection furnished dihydrodehydrodiconiferyalcohol in 60% overall yield, >95:5 dr and 93:7 er, accomplishing a much more e cient and stereoselective synthesis than previously reported (9 steps, 23% overall yield, >95:5 dr, 93:7 er vs. 12 steps, 1.2% overall yield, >95:5 dr, 62:38 er). 69 To gain some preliminary insight into the reaction mechanism, a series of experiments were conducted (Figure 7). Kinetic experiments revealed that in the transformations of allylbenzenes and 1,4-dienes, allylic C-H bond cleavage might not be the rate-determining step.…”
Section: Resultsmentioning
confidence: 99%
“…Borane addition to TS1 followed by alkaline oxidation led to the primary alcohol TS2 in 80%. 28 The hydroxyl group is confirmed in the IR spectrum by the -OH stretch band noticed at 3350 cm -1 and the singlet at d 1.65 ppm in 1 H NMR spectrum. By a reaction of TS2 with mesyl chloride, 29,30 the nucleophilic attack of sodium azide was further favored furnishing the desired alkyl azide TS4.…”
Section: Chemistrymentioning
confidence: 90%
“…Hemelaere et al. recount the use of a cross‐metathesis/isomerization/allylboration sequence followed by an intramolecular Mitsunobu process for the diastereoselective synthesis of trans ‐2,3‐disubstituted dihydrobenzofurans 156 from diols 155 (Scheme ) …”
Section: Synthetic Routes To Coumaransmentioning
confidence: 99%